STRATEGI PENGEMBANGAN LAYANAN RUANG BACA UNTUK MENINGKATKAN MINAT BACA DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN TANAH DATAR - Fadira Auzara; Elva Rahmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the strategy for developing reading room services to increase reading interest at the Tanah Datar Regency Library and Archives Service and to identify obstacles and efforts made in its development. The study used a qualitative method with a descriptive approach. The informants consisted of one head of the library department and four librarians selected using purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed using the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the strategy for developing reading room services includes storytelling activities, group visits, organizing events, providing educational games, and promotions. Obstacles to developing children's reading room services include budget constraints, the lack of a separate or partitioned children's reading room, limited facilities and educational games, and the suboptimal expansion of the children's book collection. This study indicates that the development of reading room services requires support from innovative literacy programs and adequate facilities and infrastructure.